Tugas dan Fungsi Kepala Sekolah Dalam Memajukan Pendidikan di Bidang Administrasi - fathur rohman (Pena Islam Jurnal Pendidikan Agama Islam, 2019)
Principals as educational administrators are responsible for the smooth running of education and teaching in schools, therefore specifically school principals must have the ability to manage the curriculum, manage student administration, personnel, infrastructure, and financial administration. A school principal has a role in leadership that is very influential in the school environment for which he is responsible. The principal's job as the leader is to help the teachers develop their abilities to the maximum and create a healthy atmosphere of school life and encourage teachers, administrative staff, students and parents to unite the will, mind, and actions in effective collaborative activities for the achievement of school goals. A school principal has a role in leadership that is very influential in the school environment for which he is responsible. The principal's job as the leader is to help the teachers develop their abilities to the maximum and create a healthy atmosphere of school life and encourage teachers, administrative staff, students and parents to unite the will, mind, and actions in effective collaborative activities for the achievement of school goals.